2023
DOI: 10.3389/fnut.2023.1102146
|View full text |Cite
|
Sign up to set email alerts
|

Advances in health-promoting effects of natural polysaccharides: Regulation on Nrf2 antioxidant pathway

Abstract: Natural polysaccharides (NPs) possess numerous health-promoting effects, such as liver protection, kidney protection, lung protection, neuroprotection, cardioprotection, gastrointestinal protection, anti-oxidation, anti-diabetic, and anti-aging. Nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant pathway is an important endogenous antioxidant pathway, which plays crucial roles in maintaining human health as its protection against oxidative stress. Accumulating evidence suggested that Nrf2 antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 209 publications
0
5
0
Order By: Relevance
“…Therefore, the reduction of oxidative stress damage through elevation of antioxidant levels such as SOD and GSH, along with inhibition of MDA production, contributes to alleviating depressive symptoms in PSD. Moreover, nuclear factor erythroid 2-related factor 2 (Nrf2), a transcription factor, emerges as a pivotal regulator of antioxidant signaling pathways and holds promise as a therapeutic target for depression (Bouvier et al, 2017;Zuo et al, 2022;Luo et al, 2023). It has been observed that conventional pharmaceutical drugs exhibit limited efficacy in alleviating symptoms and may even induce severe adverse reactions in 30%-60% of patients (Liang et al, 2021).…”
Section: Polysaccharides Regulate the Oxidative Stressmentioning
confidence: 99%
“…Therefore, the reduction of oxidative stress damage through elevation of antioxidant levels such as SOD and GSH, along with inhibition of MDA production, contributes to alleviating depressive symptoms in PSD. Moreover, nuclear factor erythroid 2-related factor 2 (Nrf2), a transcription factor, emerges as a pivotal regulator of antioxidant signaling pathways and holds promise as a therapeutic target for depression (Bouvier et al, 2017;Zuo et al, 2022;Luo et al, 2023). It has been observed that conventional pharmaceutical drugs exhibit limited efficacy in alleviating symptoms and may even induce severe adverse reactions in 30%-60% of patients (Liang et al, 2021).…”
Section: Polysaccharides Regulate the Oxidative Stressmentioning
confidence: 99%
“…The evolutionarily conserved endocrine insulin/IGF-1-like signaling (IIS) pathway and mitogen-activated protein kinases (MAPK) signaling pathway both have functional effects against oxidative stress . Natural EPS activates the Nrf2/HO-1/PPAR-γ signaling pathway and concerning factors like Keap1, HO-1, and NQO1 are regulated in vivo to enhance resistance to oxidative stress . Hence, EPS regulates multiple signals and elements associated with the Keap1-Nrf2-ARE antioxidant response pathway, thereby adjusting the levels of relevant genes and proteins in response to oxidative stress.…”
Section: Antioxidant Mechanism Of Lab-derived Eps In Human Bodymentioning
confidence: 99%
“…59 Natural EPS activates the Nrf2/HO-1/PPAR-γ signaling pathway and concerning factors like Keap1, HO-1, and NQO1 are regulated in vivo to enhance resistance to oxidative stress. 60 Hence, EPS regulates multiple signals and elements associated with the Keap1-Nrf2-ARE antioxidant response pathway, thereby adjusting the levels of relevant genes and proteins in response to oxidative stress.…”
mentioning
confidence: 99%
“…31 Polyphenols, with di/tri hydroxyphenyl as the most basic expression structure, are ubiquitous in natural plants and marine organisms and come in many varieties. [32][33][34] Typical polyphenols are represented by polydopamine (PDA), tannic acid (TA), and gallic acid (GA), [35][36][37] and also include tea polyphenols, laccase, plant flavonoids, etc., [38][39][40] which have many distinct properties such as hydrophilicity, 41 adhesion, 42,43 secondary reactivity, 44 photothermal property, 45,46 etc. These excellent properties endow polyphenol-based photothermal materials with many advantages to environmentally develop high-performance PIES, and more and more relevant and important studies have been reported most recently, leading the next hotspot and frontier.…”
Section: Introductionmentioning
confidence: 99%